PENGEMBANGAN ELECTRONIC MODULE (E-MODUL) INTERAKTIF BERBASIS KEARIFAN LOKAL DI KABUPATEN SOPPENG SULAWESI SELATAN PADA MATA PELAJARAN IPAS MURID KELAS IV - Wulandari, Sri; Nur Aisyah Rivai, Immawati; Suhardiman; Rosdiana; Fajri Basam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to: 1) identify the characteristics of developing an interactive e-module based on local wisdom for the Grade IV IPAS (Natural and Social Sciences) subject at SDN 15 Jolle; 2) determine the validity level of the local wisdom-based interactive e-module; 3) determine the practicality level of the local wisdom-based interactive e-module; and 4) determine the effectiveness level of the local wisdom-based interactive e-module. The research employs the Research and Development (R&D) method using the Four-D (4D) development model, comprising the stages of define, design, develop, and disseminate. The research subjects were 15 Grade IV students at SDN 15 Jolle. Data collection techniques included questionnaires, learning outcome tests, and observations. Research instruments consisted of expert validation sheets, teacher and student response questionnaires, learning outcome test questions, and learning implementation observation sheets. The results indicate that: 1) the characteristics of the interactive e-module involve a digital teaching material in the form of a flipbook that integrates local wisdom and features interactive elements accessible via digital devices, developed using the 4-D model; 2) the e-module's validity level fell into the